PEN GAWETAN KAYU MANGIUM SECARA RENDAMAN PANAS-DINGIN DENGAN BAHAN PENGAWET BORON DAN CCB - Djarwanto Djarwanto; R Sudradjat (Jurnal Penelitian Hasil Hutan, 2002)
Wood materials from plantation timber, among others is mangium (Acacia mangium Willd.) are supposed to be more susceptible to the wood-degrading organisms. This situation can expectedly be overcome by improving wood durability through a proper preservation. Previous study of the preservation of mangium wood was only by cold soaking treatment, using boron preservative. In order to provide a complete practical guidance of wood preservation, it would be necessary to study the preservation of such mangium by hot-cold treatment with not only boron but also CCB (copper-chrome-boron) preservatives.Mangium wood samples, after reaching their air-dry condition in block-shaped size measuring 5cm by 5cm by 100cm were treated by hot-cold soaking separately in solution of boron and CCB preservatives, varying at consecutively 5 percent, 7,5 percent and 10 percent. The treatment in this regard was implementing a particular schedule, which involved the regulation of soaking durations and temperatures. The durations in the hot-soaking stage for each preservative strength were 1 hour, 2 hours and 3 hours, with the temperature maintained at 65 to 70 °C. In the following cold-soaking stage, the durations were fixed for one day.The results showed that mangium wood treated with hot-cold soaking in either boron or CCB solution and implementing such particular schedule was only applicable for indoor uses, i.e. being under the roof utilization without ground contact. In this matter, the optimum strength for boron as well as CCB preservatives was 10 percent whereby the durations of hot-soaking stage were from one and three hours, followed by cold-soaking stage for one day.